Use of Ursodeoxycholic Acid (UDCA) in the Prevention of Gallstone Disease After Bariatric Surgery – A Literature Review - Grześkowiak, Martyna; Jagodzińska , Julita; Juchniewicz, Agata; Sapikowski, Jakub; Janiszewska, Maria; Kuba, Iga; Idziński, Jakub; Lubomska, Anna; Jętasiewicz, Igor; Góralczyk, Mikołaj (Quality in Sport, 2026)
The aim of this study was to evaluate the efficacy of ursodeoxycholic acid (UDCA) in the prevention of gallstone disease in patients after bariatric surgery. The review covered scientific literature from 2016 to 2024, including four randomized controlled trials, two meta-analyses, and one retrospective study, examining the use of UDCA following procedures such as sleeve gastrectomy (SG), Roux-en-Y gastric bypass (RYGB), and one-anastomosis gastric bypass (OAGB). A standard dose of 500–600 mg/day was used, most commonly for six months postoperatively. The results demonstrated a significant reduction in the incidence of gallstone disease, particularly after SG, with a decrease from 25–37% in control groups to 7–12% in UDCA-treated groups. The studies confirmed good drug tolerance and a low incidence of adverse effects, with the main issue being non-adherence to recommendations at higher doses. The findings clearly indicate that UDCA is an effective and safe method for the prophylaxis of gallstone disease after bariatric surgery, with an optimal duration of administration of six months.